Global sagittal spinal alignment in patients with degenerative low-grade lumbar spondylolisthesis. (12th November 2019) - Kobayashi, Hiroto; Endo, Kenji; Sawaji, Yasunobu; Matsuoka, Yuji; Nishimura, Hirosuke; Murata, Kazuma; Takamatsu, Taichiro; Suzuki, Hidekazu; Aihara, Takato; Yamamoto, Kengo
Purpose: Global sagittal spinal alignment undergoes changes on the basis of sagittal malalignment (trunk inclined forward) in natural degenerative progression. We hypothesized that this change would associate with the disease state of the degenerative lumbar spondylolisthesis (DS). This study aimed to evaluate the global sagittal spinal alignment of low-grade DS by classifying in accordance with sagittal vertical axis (SVA). Methods: The DS group was classified into three types according to the adult spinal deformity classification: type 1, SVA < 40 mm; type 2, 40 mm ≤ SVA < 95 mm; and type 3, 95 mm ≤ SVA. Age and sagittal spinal parameters (thoracic kyphosis, lumbar lordosis (LL), sacral slope (SS), pelvic tilt (PT), and pelvic incidence (PI)) were compared among three types. Results: There were statistically significant differences in age, LL, PI, and PT among the three types. In comparison between two types, there was a statistically significant difference between type 1 and type 2 and between type 1 and type 3, but not between type 2 and type 3 in these parameters. PI tended to increase as the type increases. Furthermore, there was significant difference between types 1 and 3. Conclusion: We evaluated the features of the DS types classified by sagittal alignment. Large PI is one of the risk factors for SVA deterioration of DS. PI may be involved in the onset and progression of DS.